Linking laboratory air quality to workers’ psychological performance in Malaysian university laboratories - Puteri Balqis Mohd Hatta; Muhammad Nazman; Nur Faseeha Suhaimi (International Journal of Occupational Safety and Health, 2025)
Introduction: Poor indoor air quality (IAQ) in laboratories can negatively impact worker comfort and psychological well-being. This study investigates the relationship between IAQ and psychological performance among laboratory workers in Malaysia.